Experimental studies of groundwater pipe flow network characteristics in gravelly soil slopes - Wang, Zhi-lei (2013)
Piping flow networks have often been identified in hydrogeological field studies of gravelly soil slopes in the southern part of China. The present experimental studies have shown that under long-term groundwater seepage, piping flow networks gradually develop in the slope. Factors affecting the development of flow pipe seepage network included the grain size distribution, the degree of soil compaction, and soil depth. Piping seepage networks favorably form if the content of the gravel was high, the soil cohesion was low, the degree of the soil compaction was low, or the soil depth was shallow. Due to the enhanced permeability associated with the presence of flow pipe seepage network in gravelly soil slopes, groundwater can be effectively drained away. This can beneficially prevent the rise of groundwater level in the slope during raining seasons, hence reducing pore water pressure along the potential failure surface and increasing slope stability. Once the flow pipe seepage network was disturbed or damaged, the water level in the upper portion of the slope experienced a great rise, hence reducing the slope stability. Therefore, slope toe excavation and excessive loading at the slope crest should be avoided for slopes with well-developed flow pipe seepage network in order to preserve it.